trnL-trnF gene region analysis of natural Curuligio orchioides collected in Thua Thien Hue - Bùi, Lê Thanh Nhàn; Trương, Thị Bích Phượng; Hoàng , Tấn Quảng (Hue University Journal of Science: Natural Science, 2023)
Curculigo orchioides, a member of the genus Curculigo and the family Hypoxidaceae, is a herbal plant and has been used as traditional medicine. Currently, there is high demand for cultivating this plant. However, there has not been sufficient research into the genetic diversity to assist the authentication of the material, for example, the genetic research based on the DNA indicators of Curculigo. In this study, the gene trnL-trnF region of 15 Curculigo orchioides germplasms collected from three locations in the province were sequenced and analyzed for identification and evolution. The results show that the sequenced fragment of the gene trnL-trnF from the surveyed samples has 99% similarity and 100% coverage compared with the NC 053892 sequence of Curculigo orchioides. We identified five haplotypes of C. orchioides in the province with a haplotype diversity coefficient (Hd) of 0.705 ± 0.088. The genetic distances ranged from 0 to 0.49% among the populations. The Curculigo orchioides population in Thua Thien Hue has evolved towards balanced, neutral, and random selection because of the lack of rare alleles.